2001
DOI: 10.1086/318388
|View full text |Cite
|
Sign up to set email alerts
|

The Milky Way in Molecular Clouds: A New Complete CO Survey

Abstract: New large-scale CO surveys of the Ðrst and second Galactic quadrants and the nearby molecular cloud complexes in Orion and Taurus, obtained with the CfA 1.2 m telescope, have been combined with 31 other surveys obtained over the past two decades with that instrument and a similar telescope on Cerro Tololo in Chile, to produce a new composite CO survey of the entire Milky Way. The survey consists of 488,000 spectra that Nyquist or beamwidth sample the entire Galactic plane over a (1 8 ¡) strip 4¡È10¡ wide in la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

178
2,713
18
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,120 publications
(2,951 citation statements)
references
References 84 publications
178
2,713
18
4
Order By: Relevance
“…Clouds on stable orbits in the central molecular zone (r GC ≤ 200 pc) are suggested to follow spheroidal x2 orbits in the Milky Way bar potential (e.g., Binney et al 1991, Englmaier andGerhard 1999). Molecular clouds with high densities capable of massive cluster formation display line-of-sight velocities of v los < 120 km/s in radio CS surveys (Dame et al 2001). A velocity of 120 km/s is in agreement with the terminal velocity of x2 orbits in the Milky Way bar potential.…”
Section: Formation Scenarios For the Archessupporting
confidence: 60%
See 1 more Smart Citation
“…Clouds on stable orbits in the central molecular zone (r GC ≤ 200 pc) are suggested to follow spheroidal x2 orbits in the Milky Way bar potential (e.g., Binney et al 1991, Englmaier andGerhard 1999). Molecular clouds with high densities capable of massive cluster formation display line-of-sight velocities of v los < 120 km/s in radio CS surveys (Dame et al 2001). A velocity of 120 km/s is in agreement with the terminal velocity of x2 orbits in the Milky Way bar potential.…”
Section: Formation Scenarios For the Archessupporting
confidence: 60%
“…Candidates for such a collision are clouds on x1 orbits following the bar's major axis outside the x2 (minor axis) orbital zone, as already suggested by Binney et al 1991, or clouds falling in from the outer parts of the Galaxy (Crawford et al 2002). A collision between an x1 and an x2 orbit cloud is particularly intriguing, as x1 clouds display line-of-sight velocities of up to 270 km/s (Dame et al 2001), which could account for the orbital velocity of 232 km/s observed for the Arches today. One particular problem with this scenario is that the cluster would need to inherit the high velocity of the infalling cloud, which requires a massive, high density cloud capable to transfer its momentum to the local cloud on the x2 orbit.…”
Section: Formation Scenarios For the Archesmentioning
confidence: 88%
“…HESS excess counts image (> 100 GeV) towards HESS J1825−137 overlaid by the CO(1-0) integrated intensity contour (40,60,80, 100 K km/s) between v lsr = 40 − 60 km/s from Dame, Hartmann & Thaddeus (2001) as revealed by Lemiere, Terrier & DjannatiAtaï (2006). The white circles represent the different SNRs detected (Brogan et al 2006).…”
Section: Carbon Monosulfide Cs(1-0) and Isotopologuesmentioning
confidence: 96%
“…The list consists of 44 star-forming regions with precise astrometry, from which we determine the basic structure of the Galaxy (Honma et al 2012). In figure 2, we show distributions of 44 star-forming regions in the l-v diagram of the Galaxy, overlaid on the CO l-v diagram (Dame et al 2001). As seen in figure 2, the sources are basically distributed in the northern part of the Galaxy, with a hole around the region between l = 240 • to 350 • due to the bias in array location.…”
Section: Galactic Structurementioning
confidence: 97%